2015
DOI: 10.1002/cam4.513
|View full text |Cite
|
Sign up to set email alerts
|

ABO non‐O type as a risk factor for thrombosis in patients with pancreatic cancer

Abstract: ABO blood type has previously been identified as a risk factor for thrombosis and pancreatic cancer (PC). The aim of the study is to demonstrate the associations between ABO blood type and other clinical factors with the risk of thromboembolism (TE) in patients with PC. We conducted a retrospective study in 670 patients with pathologically confirmed pancreatic adenocarcinoma at the University of Texas MD Anderson Cancer Center. Clinical information was retrieved from medical records. ABO blood type was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 29 publications
0
27
2
1
Order By: Relevance
“…It is already known that ABO blood types are associated with the risk of VTE not only in unprovoked cases12, but also in provoked cases, such as cancer1314, pregnancy15, trauma16 or post-surgery1718. Meta-analysis showed that the prevalence of non-O blood types is higher in unprovoked VTE cases (OR = 1.88) than in provoked cases (OR = 1.33)3.…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that ABO blood types are associated with the risk of VTE not only in unprovoked cases12, but also in provoked cases, such as cancer1314, pregnancy15, trauma16 or post-surgery1718. Meta-analysis showed that the prevalence of non-O blood types is higher in unprovoked VTE cases (OR = 1.88) than in provoked cases (OR = 1.33)3.…”
Section: Discussionmentioning
confidence: 99%
“…This 5-SNP score performed similarly to the score of all 31 SNPs, 20 and detected subjects at increased risk of both incident and recurrent VTE. [20][21][22] Genetic alterations such as Factor V Leiden, 23,24 ABO rs505922 and rs8176746, 25 ABO rs8176719, 26 and prothrombin G20210A [27][28][29][30] have all been found to be associated with VTE risk in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Adult studies have identified non‐O blood group as a risk factor for venous TE and that inherited thrombophilia increases the risk conferred by non‐O blood group . A meta‐analyses of 38 studies showed that non‐O blood group was the most common genetic prothrombotic risk factor especially in combination with FVL .…”
Section: Introductionmentioning
confidence: 99%